MEASUREMENT OF DEVELOPMENT & CAUSES OF UNDERDEVELOPMENT IN AFRICA - Riak , Dr Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Measuring development is very complicated. This is due to the fact that development itself is multidimensional phenomena, which encompass all the social, economic, political and cultural dimensions. Different units of measurements measure each of this. This makes it impossible to get an overall indicator for the development situation or state of a particular country, unless we resort to some statistical techniques e.g. standardization and normalization whereby we can get an overall indicator. Usually when measuring development, we need to distinguish between Economic indicators and Non economic indicators. The Economic indicators are usually measured in terms of the national income estimates or per capita income. The national income refers to the total value of goods and services produced or generated by an economy during a certain period of time usually one year. However, it has its own drawbacks: Not all countries use the same method in the calculation or estimation of the national income. g. firstly some countries use the output method. In this they estimate what is produced by each sector and translate into monetary value and then obtain the national income; secondly other countries use the income method where we add the factors’ return e.g. labour, land, capital and entrepreneurship. We can get the national income from these factors; thirdly we may use the expenditure method. In this we simply add the total expenditure of economy or investment expenditure from imports and exports and determine the balance of payments. These three methods are used differently in different countries, but their estimates are different. This complicates the international comparison of development levels. Usually a country chooses one of these methods depending on the nature of the economy and also the database. The exchange rates can also be used for determining monetary value. This however, differs from one country to another. Some activities under certain social set ups are not included as economic activities e.g. women’s housework and other related informal activities. There are some statistical errors in the calculation of national income. Considering the non-economic indicators we have social, political, cultural aspects of life. The UN institute for Social Development specified certain non-economic indicators of development. These have different units of measurement where we weigh and add them up to show the indicator.